The Creation of Anti-Corruption Application for Youth Based on the Concept of Upright School Project - ทองจันทร์ ผการัตน์ (Princess of Naradhiwas University Journal, 2018)
The objectives of this study were: 1) to study and create an anti-corruption application for the youth, 2) to assess the effectiveness of the anti-corruption application, and 3) to compare the learning achievements before and after using the anti-corruption application. Sample was 43 secondary students (14 years old) in theirsecond semester of academic year 2016 at Anubannarathiwat School. Participants were selected by simple random sampling. The research instruments consisted of: 1) a structured interview for 15 representative teachers who attended the Upright School Project, 2) a learning management plan, 3) the anti-corruption application and 4) achievement tests after learning through the application. The research instruments were qualified for validity, yielding reliability of 0.90. Data were analyzed by using mean, standard deviation and t-test. The content of the anti-corruption application were divided in 4 parts including discipline, loyalty, living in contentment and public mind. Results were as follows: 1) global effectiveness of application was at 85.00/85.70, 2) learning achievement revealed that the post-test scores of using the anti-corruption application were statistically significantly higher than the pre-test scores (p < 0.05). It can be concluded that the anticorruption application for youth in accordance with the concept and objective of the upright school project in terms of the technology that creates educational innovation. It also enhances the accessibility of educational application– anytime, anywhere without the learning limitations.